2017
DOI: 10.1128/jvi.00278-17
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10/CXCR3-Dependent Mobilization of Herpes Simplex Virus-Specific CD8 + T EM and CD8 + T RM Cells within Infected Tissues Allows Efficient Protection against Recurrent Herpesvirus Infection and Disease

Abstract: Herpes simplex virus 1 (HSV-1) establishes latency within the sensory neurons of the trigeminal ganglia (TG). HSV-specific memory CD8 ϩ T cells play a critical role in preventing HSV-1 reactivation from TG and subsequent virus shedding in tears that trigger recurrent corneal herpetic disease. The CXC chemokine ligand 10 (CXCL10)/CXC chemokine receptor 3 (CXCR3) chemokine pathway promotes T cell immunity to many viral pathogens, but its importance in CD8 ϩ T cell immunity to recurrent herpes has been poorly elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 84 publications
1
32
0
Order By: Relevance
“…64 In addition to cytokines, chemokines are also important in the trafficking and localization of T RM cells. For example, the chemokine receptors CXCR6 and CCR10 are required for optimal formation of a T RM population in the skin; lack of either CXCL10 or CXCR3 compromises the mobilization of T RM cells within latently infected trigeminal ganglia and results in the absence of signals required for differentiation 15,65,66 ; CXCR3 is also critical for T cell accumulation in uninfected salivary glands, 67 and CXCL17 is required for the mobilization of T RM cells in the vaginal mucosa (VM). 68 Differentiation of recirculating T EM cells depends on prolonged cognate antigen stimulation.…”
Section: Differentiation and Maintenance Of Cd8 + T Rm Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…64 In addition to cytokines, chemokines are also important in the trafficking and localization of T RM cells. For example, the chemokine receptors CXCR6 and CCR10 are required for optimal formation of a T RM population in the skin; lack of either CXCL10 or CXCR3 compromises the mobilization of T RM cells within latently infected trigeminal ganglia and results in the absence of signals required for differentiation 15,65,66 ; CXCR3 is also critical for T cell accumulation in uninfected salivary glands, 67 and CXCL17 is required for the mobilization of T RM cells in the vaginal mucosa (VM). 68 Differentiation of recirculating T EM cells depends on prolonged cognate antigen stimulation.…”
Section: Differentiation and Maintenance Of Cd8 + T Rm Cellsmentioning
confidence: 99%
“…68 Significant increases in both the number and function of HSV-specific CXCR3 + T RM cells have been detected in the trigeminal ganglia of mice following UV-B-induced HSV-1 reactivation, which protects the host from recurrent HSV infection, and a lack of T RM is again associated with recurrent ocular HSV infection. 65 In addition, accumulation of T RM cells in the skin provides enhanced control against viral infection with HSV-1. 11,62,82 T RM cells generated by the "prime and pull" protocol may reduce the spread of infectious HSV-2 into the sensory neurons and prevent development of clinical disease.…”
Section: Cd8 + T Rm Cells In Anti-viral Immunitymentioning
confidence: 99%
“…Of these, the CD4 + and CD8 + T cells have been shown to be important for resolution of the acute infection [44] and CD8 + T cells directed against an epitope on glycoprotein B are hypothesized to maintain the latent state [76] and there is evidence that this is dependent on MHC class I expression [77]. Further, CXCR3 + CD8 + T cells have been shown to increase in the TG and the epithelial surface following a reactivation stimulus and this correlated with a decrease in viral shedding at the surface, noting that outcomes in the TG were not examined [78]. It has also been proposed that regulatory T cells function to suppress CD8 + T cells and facilitate HSV reactivation [79].…”
Section: Discussionmentioning
confidence: 99%
“…Prime-and-pull was developed to establish local tissue Trm cells at target sites by parenterally vaccinating to elicit systemic T cell responses (prime) and then to recruit activated T cells to specific tissues with a topical chemokine (66) or with nonspecific inflammation (67) (pull), where such T cells could become Trm cells and mediate protection. Methods have been reported for the liver (19), urogenital tract (66,68,69), and lungs (70,71). The recent malaria prime-and-trap report showed that TCR transgenic cells adoptively transferred into naive recipient mice could be primed with peptide-pulsed DCs and then trapped with a liver-specific, Ag-expressing recombinant adeno-associated virus (19).…”
Section: Discussionmentioning
confidence: 99%